The first important aspect of this problem is order of operations. This you should know as multiplication and division before addition and subtraction.
So first, you would distribute the -4 on the left side of the equation:
-4f -24 + 14 = 20
Then, you would combine like terms on the left side, like terms are values that have the same variable:
-4f -10 = 20
You would then add 10 to both sides of the equation, in order to start isolating the f variable:
-4f = 30
Lastly, to completely isolate the f, divide both sides of the equation by -4:
f = ...
2007-05-18 09:56:51
·
answer #1
·
answered by Joy M 7
·
2⤊
0⤋
The objective is to determine the value of 'f'. Multiplication first, then addition. The product of -4 and 'f' is '-4f'. The product of -4 and +6 is -24. Summing your real numbers, -24 and +14, the left side of the equation becomes -4f - 10, sending -10 to the right side by adding it to 20, the over all equation becomes -4f = 30
30 divided by -4 = -7.5
f = -7.5
2007-05-18 17:02:13
·
answer #2
·
answered by D 2
·
0⤊
0⤋
Use the distributive property and multiply the negative four with the f and negative four with the six. So far you have
-4f-24+14. Now, add the similar terms. -4f-10=20. Using the symbolic method, add ten to both sides of the equation and you have -4f=30. Divide -4 to both sides to get f by itself. Your answer is thirty over negative four.
2007-05-18 17:02:32
·
answer #3
·
answered by Rachel R 2
·
0⤊
0⤋
First you need do distributed the parenthesis so it reads
-4f-24+14=20
then you add the -24 and 14 together
-4f-10=20
then add the 10 to both sides to get it on the other side
-4f=30
Finally you divide by -4 to get the final answer at
f= -7.5
2007-05-18 16:55:35
·
answer #4
·
answered by starrchick101 3
·
1⤊
0⤋
-4(f+6) + 14 =20
-4f-24+14=20
-4f=30
f=-15/2
2007-05-18 17:06:13
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
-4(f+6) + 14 =20
Simplify left side
-4f - 24 +14 = 20
Combine terms
-4f - 10 = 20
Add 10 to both sides
-4f = 30
Divide thru by -4
f = -7.5
.
2007-05-18 16:59:14
·
answer #6
·
answered by Robert L 7
·
1⤊
0⤋
multiply brackets out:
-4f - 24 +14 =20
tidy up:
-4f = -30
f =-30/4
Ans: f =-7.5
2007-05-18 17:02:24
·
answer #7
·
answered by BB 7
·
0⤊
0⤋
-4f-24+14=20
-4f-10=20
-4f-10+10=20+10
-4f=30
-4f/-4=30/-4
f=-7.5
2007-05-18 16:59:54
·
answer #8
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
undo what was done to the variable:
-4(f+6) + 14 = 20 .......... subtract 14
-4(f + 6) = 6 .................. divide by -4
f + 6 = -1.5 ................... subtract 6
f = -7.5
2007-05-18 16:58:13
·
answer #9
·
answered by Philo 7
·
0⤊
2⤋